THE MAIN TASKS OF THE PARLIAMENT TO ENSURE STATE POLITICAL SECURITY IN ACCORDANCE WITH THE CONSTITUTION OF THE REPUBLIC OF UZBEKISTAN - Sarvar Kholikov (Scholar Express Journals, 2022)
The parliamentary system as a form of political system is considered. The topicality of the concept of the parliamentarism phenomenon that would include a clear understanding of the very essence of parliament and its relationship with different state-legal categories in terms of the political system of states is highlighted. The very essence of the parliament system, as well as its role in the formation and influence on the system of state and national security is analyzed. Determined by complex research of theoretical and practical problems of the role of parliament in the system of state power, mutual relations of legislature with other branches of the state power, the maintenance of balanced and stable equilibrium between legislative, executive and judicial branches of state power in conditions of renewal and the further democrati-zation of the state administration and modernization of the country.
Keywords: power; functions of parliament; renewal; administration